Efeito de um programa de treinamento de enfermeiros acerca da segurança alimentar e uso dos alimentos regionais no Nordeste Brasileiro - Ferreira, Adria Marcela Vieira (2018)
This study was intended to assess the effectiveness of a nurse training program on food safety and regional food in the northeastern region in Brazil. This was a quasi-experimental research, typified as before-and-after, which was based on the intervention of a training program conducted with eight nurses who work in the Family Health Strategy (FHS) in the countryside of Maranguape/Ceará. The training program happened in six steps and was assessed under the four levels of training assessments suggested by Kirkpatrick and Kirkpatrick (2010): reaction, learning, behavior and results. Data collection took place with the eight nurses from the training program, with the application of the serial album “Regional food promoting food safety”, in such a way as to enable us to assess their reaction, learning and behavior in the workplace after training. Data collection also took place with the 62 mothers of children in early childhood who attended the educational interventions performed by the nurses trained during the training program, thereby providing the assessment of results, through the application of the knowledge survey called attitude and practice on regional food, in four moments: before and immediately after the educational intervention; one month, three months and six months after the educational intervention. The research project was approved by the Research Ethics Committee of the Federal University of Ceará. The results of this study highlighted a positive reaction assessment from the surveyed nurses to the training, based on reports of learning, mastery of educational technology and satisfaction in using it to promote both food safety and use of regional food by families. When assessing the nurses’ learning, we found an average of 83.6% of right answers in the pre-test of knowledge, and we also noted an increase to 92.3% in the second post-test, which was considered as a very good average of right answers. When assessing the nurses’ behavior, we checked the use of the educational technology in their work environment and the acquisition of new knowledge and skills, since we noted the accomplishment of a total of 30 activities with the use of the serial album, with a predominance of the accomplishment of individual activities (83.3%) compared to group activities (16.7%). When assessing the results, we noted that the educational intervention held by nurses together with mothers provided an increase in the mothers’ appropriate knowledge, attitude and practice (KAP) axes on regional food, with statistical significance for the practice axis (p=0.022). Regarding sociodemographic variables, there was no statistically significant association with the KAP axes; however, we noted that mothers with lower schooling level were more likely to show inappropriate knowledge (OR=5.00), inappropriate attitude (OR=9.61) and inappropriate practice (OR=2.97). Similarly, mothers with lower income were more likely to have inappropriate knowledge (OR=5.57) and inappropriate practice (OR=2.42). We conclude that the training program was effective, since nurses obtained positive reaction, better learning, and behavior change; moreover, mothers have shown satisfactory results in the knowledge, attitude and practice axes after the intervention with the educational technology held by nurses.